Faktor-faktor yang mempengaruhi penjanaan trip ke tempat kerja dan kesan pelaksanaan teleworking dalam mengurangkan pencemaran udara - Haron, Norhazlan (2005)
Teleworking is a new way of working based upon information and communication technologies which is rapidly replacing the old method of working in the cities. In most developed countries including the United States, United Kingdom and Canada, this new way of working has managed to help reduce the problem of traffic congestion and air pollution due to work related trip generated from private vehicles entering the cities. The rapid growth of residential landuse in urban fringe has caused the CBD area to continue to function as the employment center of the population forcing office workers to generate trips to their offices in the cities. The large movement of private vehicles entering the city centre area contributes to the rapid increase of CO, NOx, HC emissions thus affecting the general health condition of the urban population. In addition, it also increases the traffic congestion in already congested city. In addition, office workers’ need to bear travel related cost such as car park, fuel and maintenance costs. The purposes of this study are firstly to determine that influence trip generation among the workers and secondly to assess the impacts of teleworking in reducing air pollution. Two hypotheses were generated in this study. First, the location of residences in urban fringe will influence the number of trips generated and their tendency to telework. Secondly, their willingness to adopt teleworking will help reduce air pollution through the decrease in work trip. A questionnaire survey was undertaken among 200 private sector offices worker in Johor Bahru CBD area. Informations obtained are divided into two parts which are the characteristics of the respondents and the factors that contribute to trip generation. Data collected from respondents were analyzed using standard statistical techniques such as frequency distribution, cross tabulation and the Chisquare. The study has shown that 75% (150) of the respondents has some knowledge about the practice of teleworking and are willing to adopt it. The home location of the respondents at the urban fringe with more than 10 km distance and the time taken to travel to work act as the main reasons for the respondents to choose teleworking. In addition, traffic congestion, air pollution and the cost related to travel to work are other reasons. It can be concluded that the acceptance of teleworking will help reduce trip generation and hence the level of pollution in the city.